1995
DOI: 10.1093/oxfordjournals.humrep.a135992
|View full text |Cite
|
Sign up to set email alerts
|

Infertility: Hydrosalpinges in in-vitro fertilization: an unfavourable prognostic feature

Abstract: The aim of this study was to determine whether the presence of a hydrosalpinx influences in-vitro fertilization (IVF) prognosis. Comparisons were made between 69 IVF cycles in 37 patients carrying hydrosalpinges (hydrosalpinx group) and 67 IVF cycles in 41 patients without tubes or surgically sterilized (control group). Twenty-two patients carrying hydrosalpinges underwent salpingectomy or salpingoplasty (operated group); they then underwent 42 IVF trials which were compared with the two former groups. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
83
0
6

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(99 citation statements)
references
References 12 publications
10
83
0
6
Order By: Relevance
“…The third pathology was bilateral hydrosalpinx. In the literature there is a consensus that hydrosalpinx adversely affects the outcome of IVE The suggestion is that toxic substances and inflammatory cellular elements coming from the dilated tube can adversely influence the implantation of the embryo (22)(23)(24). With these observations taken into account, it seems that laparoscopy may have been important for the ICSI treatment of 2 (2.6%) of 76 couples.…”
Section: Discussionmentioning
confidence: 99%
“…The third pathology was bilateral hydrosalpinx. In the literature there is a consensus that hydrosalpinx adversely affects the outcome of IVE The suggestion is that toxic substances and inflammatory cellular elements coming from the dilated tube can adversely influence the implantation of the embryo (22)(23)(24). With these observations taken into account, it seems that laparoscopy may have been important for the ICSI treatment of 2 (2.6%) of 76 couples.…”
Section: Discussionmentioning
confidence: 99%
“…2 Center for Advanced Research in Human Reproduction, Infertility and Sexual Function, Urological Institute, The Cleveland Clinic Foundation, 9500 Euclid Avenue, A81 Cleveland, Ohio 44195. 3 Center for Advanced Research in Human Reproduction, Infertility and Sexual Function, Department of Biostatistics and Epidemiology, The Cleveland Clinic Foundation, 9500 Euclid Avenue, A81 Cleveland, Ohio 44195.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effect of hydrosalpinges was reversible by salpingectomy prior to IVF (1)(2)(3)(4)(5). The flow of hydrosalpingeal fluid (HSF) into the endometrial cavity may lead to mechanical flushing of the embryos from the uterus (6).…”
Section: Introductionmentioning
confidence: 99%
“…Other theories have included simultaneous damage to the endometrium at the time of the original tubal infection, influence of inflammatory substances transported through the blood or lymphatic system, and impairment of ovarian function and oocyte quality by the original infection or by the influence of toxic substances. Several studies have shown negative bacterial cultures from hydrosalpinx fluid (7)(8)(9), but other agents than microorganisms, such as lymphocytes, cytokines, prostaglandins, leukotrienes, catecholamines, and peptidergic transmitters, have been suggested to be responsible for the negative action (10,11).…”
Section: Introductionmentioning
confidence: 99%